Captura digital de movimento no cinema de animação - Joao Victor Boechat Gomide (2006)
Motion capture, also known as mocap, is an ensemble oftechniques used to map and reproduce displacements from objects andliving beings. Actually it is realized using digital devices, and it is abranch of knowledge relatively new, searching for definitions andimprovements in the technique, that is growing in various directions. It isused in animations and electronic games, special effects for cinema andtelevision, dance, signal language, gestural recognition, biomechanics,medical rehabilitation, among various others. This text covers different aspects of its applications to character animation. It discusses its general characteristics and related controversies to consider it as art or not, as taxonomy questions. Afterwards it approaches its historical evolution, since human and animal mechanical studies using photographic techniques till its use in cinema. It relates the different ways to do motion capture using different physical principles. And at last it studies its applications to character animation, the advantages to use or not the technique in each situation and how to plan the production.